2015
DOI: 10.1137/140973839
|View full text |Cite
|
Sign up to set email alerts
|

Structured Eigenvalue Backward Errors of Matrix Pencils and Polynomials with Palindromic Structures

Abstract: Abstract. We derive formulas for the backward error of an approximate eigenvalue of a * -palindromic matrix polynomial with respect to * -palindromic perturbations. Such formulas are also obtained for complex T -palindromic pencils and quadratic polynomials. When the T -palindromic polynomial is real, then we derive the backward error of a real number considered as an approximate eigenvalue of the matrix polynomial with respect to real T -palindromic perturbations. In all cases the corresponding minimal struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…Only precise "local" structured backward error analyses valid for each particular computed eigenvalue or eigenpair have been developed so far. See, for example, [3,9,10,11], or [1,2] for the case of the structured linearizations in the vector spaces L 1 (P ), L 2 (P ) and DL(P ), introduced in [51,52] and [38].…”
mentioning
confidence: 99%
“…Only precise "local" structured backward error analyses valid for each particular computed eigenvalue or eigenpair have been developed so far. See, for example, [3,9,10,11], or [1,2] for the case of the structured linearizations in the vector spaces L 1 (P ), L 2 (P ) and DL(P ), introduced in [51,52] and [38].…”
mentioning
confidence: 99%
“…Matrix polynomials with special structures occur in numerous applications in mechanics, control theory, linear systems theory and computer‐aided graphic design, see References 9,10,15,18. In particular, palindromic matrix polynomials arise in the mathematical modeling and numerical simulation of surface acoustic wave filters and vibration analysis of railway tracks excited by high‐speed trains, see References 11 and 3. For obtaining the eigenvalues and eigenvectors of matrix polynomials, the most widely used approach is to linearize the given matrix polynomial into a bigger size matrix pencil (see, Reference 13 for more on linearization).…”
Section: Introductionmentioning
confidence: 99%
“…The concept of structural stability, first introduced by A. A. Andronov and L. S. Pontryagin in 1937 in the qualitative theory of dynamical systems, in the sense of structurally stable elements being those whose behavior does not change when applying small perturbation [1], has been largely studied by many authors in different contexts for example, in the scenario of Linear Algebra we can found [4], [5], [7], [8], among others.…”
Section: Introductionmentioning
confidence: 99%